Cultural Diversity Education in “Islam and Religious Moderation” Courses: Case Study in Islamic Higher Education - Karnadi; Hasanah, Silviatul; de Cómputo, Escuela Superior; Wilson, Elaine (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study investigates the implementation model of cultural diversity education within the